Strategi Kontekstual Dalam Meningkatkan Penguasaan Kompetensi Dasar Pada Mata Pelajaran Ekonomi SMAN 19 Gowa - Sri Nalda; Ira Rahayu; Catherine Febrina; Nur Amalia; Nurwahida Nurwahida; Ahyar Zacky; Ahmad Apriansyah (PT. Citra Media Publishing, 2025)
This research explores the application of contextual learning in economics learning at SMAN 19 Gowa and its impact on students' mastery of basic competencies. Using a qualitative approach with a case study design, data was collected through interviews and observation. The results show that contextual strategies increase students' interest and understanding, and strengthen their confidence in applying economic concepts. However, challenges arise when abstract material is difficult to relate to everyday experiences, especially for students from different economic backgrounds. This research concludes that contextual learning is effective, but requires adjustments to the material to meet student needs.